Structure-tuned and thermodynamically controlled mechanochromic self-recovery of AIE-active Au(i) complexes. Issue 3 (16th December 2019) - Dong, Yubao; Zhang, Jing; Li, Aisen; Gong, Junyi; He, Benzhao; Xu, Shuping; Yin, Jun; Liu, Sheng Hua; Tang, Ben Zhong
Abstract : The flexible alkyl chain-tuned and temperature-dependent self-recovery behaviors aided by molecular motions in a series of AIE-active Au(i ) complexes was investigated. Abstract : Stimuli-responsive luminescent materials, which show various luminescence alterations upon the introduction of external mechanical forces, have attracted extraordinary attention owing to their promising applications in smart materials. Amongst, the phenomena of self-recovered mechanochromic luminescence constitute only a small proportion, and relevant systematic explorations are extremely limited. Here, we developed a series of new Au(i ) complexes (AuIB-C n, n = 5–10) featuring aggregation-induced emission properties, and systematically studied their solid-state self-recovery properties. We showed that the self-recovery speed could be elaborately tuned by introducing alkyl chains of different lengths, or changing the temperature. Increasing the alkyl chain length could speed up the self-recovery due to much faster intermolecular rearrangements. Lowering the temperature allowed for the capture of the originally superfast and unobservable self-recoveries of C8–C10 due to the decreased molecular mobility. In addition, we also demonstrated the great potentials of these AIE-active complexes serving as self-erasing rewritable paper and anti-counterfeit carbonless copy paper in practical applications.